2021
DOI: 10.3390/su14010214
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Capital or Transfer Deficit: A Dual Perspective of English Learning of ESL College Transfer Students

Abstract: This research addressed a research gap in scrutinizing the language problems of English as a second language (ESL) transfer students (TSs) with regard to the aspects of “transfer deficit” and “transfer capital”, instead of simply labelling the use of English as a “transfer deficit”. One hundred and twenty-four TSs participated in this qualitative study. From qualitative content analysis, three main categories were identified: (a) English competence as transfer capital; (b) English competence as transfer defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Other studies have found that some sub-degree programs spend time equipping students with source-based writing skills (Pullen, 2019), which are important to academic literacy, but they do not have enough time to fully polish their language skills (Frodesen, 2015). Foung and Cheung (2022) also reported that students lack the disciplinary vocabulary to learn effectively in a university setting, which is echoed by Wu and Lau (2021). Lin and Yi (1997) believe that these problems become barriers for transfer students to learn effectively in their other courses.…”
Section: General Equity Issues With College Transfer Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have found that some sub-degree programs spend time equipping students with source-based writing skills (Pullen, 2019), which are important to academic literacy, but they do not have enough time to fully polish their language skills (Frodesen, 2015). Foung and Cheung (2022) also reported that students lack the disciplinary vocabulary to learn effectively in a university setting, which is echoed by Wu and Lau (2021). Lin and Yi (1997) believe that these problems become barriers for transfer students to learn effectively in their other courses.…”
Section: General Equity Issues With College Transfer Studentsmentioning
confidence: 99%
“…For example, Wu and Lau (2021) believes that college transfer students are more mature and have greater cognitive power than traditional students, so they can handle the courses in their disciplines well despite their lower language proficiency. Cheung and Foung (2021) re-examined "transfer shock" and concluded that some challenges may actually be advantages. For example, transfer students have the study skills needed to handle course readings they do not understand; they are accustomed to handling such difficult readings in their sub-degree studies.…”
Section: General Equity Issues With College Transfer Studentsmentioning
confidence: 99%
See 2 more Smart Citations